The effects of L-carnitine and fructose in improved Ham’s F10 on sperm culture in idiopathic severe asthenospermia within 24h - Dehui Chang; Fudong Li; Yindong Kang; Yixin Yan; Feiyan Kong; Wei Jiang; Dongxing Wang; Zhigang Cao; Liuting Xu; Chuang Huang; Yafen Kang; Xuejun Shang; et al. (PLoS ONE, 2025)
To study the effects of L-carnitine and fructose on semen parameters of severe asthenospermia patients by sperm culturing in vitro within 24h. We optimized the energy composition and antioxidant substances of sperm culture medium in vitro (based on Ham’s F10 culture medium) by orthogonal test for preparing high quality culture medium. Sperms of 60 patients with idiopathic severe asthenospermia were collected, and cultured in vitro within 24h, by Ham’s F10 culture medium added to different concentrations of L-carnitine and fructose and culture temperature, whose effects on sperm motility were observed to determine which is the most appropriate concentration and temperature. For determining the appropriate concentration of L-carnitine and fructose and the suitable culture temperature in Ham’s F10 culture medium, the orthogonal experiments were carried out to optimize above three factors, which had great influence on sperm viability, survival rate, deformity rate and DNA fragmentation index (DFI). The final concentration of L-carnitine and fructose was determined in terms of initial tests to assess the effects of different concentrations (4, 8, 12, and 16 mg/ml L-carnitine and 0.125, 0.250, 0.375, and 0.50 mg/ml fructose) on sperm viability and motility in culture. During the operation of processing and culturing sperms in vitro within 24h, orthogonal test showed that sperm viability was better at the final concentration of 8 mg/ml L-carnitine and 0.375 mg/ml fructose in improved Ham’s F10 culture medium at 36.5°C. Idiopathic severe asthenospermia sperm can be effectively improved by the modified Ham’s F10 culture medium of the final concentration of 8 mg/ml L-carnitine and 0.375 mg/ml fructose at 36.5°C within 24h, which has shown better culture effect and is superior to Ham’s F10 basic medium.